P097: The characteristics and effectiveness of interventions targeting chronic pain patients in the emergency department: A systematic review and meta-analysis. (May 2019) - O'Rielly, C.; Sutherland, L.; Wong, C.
Abstract : Introduction : Patients with chronic non-cancer pain (CNCP) and opioid-use disorders make up a category of patients who present a challenge to emergency department (ED) providers and healthcare administrators. Their conditions predispose them to frequent ED utilization. This problem has been compounded by a worsening opioid epidemic that has rendered clinicians apprehensive about how they approach pain care. A systematic review has not yet been performed to inform the management of CNCP patients in the ED. As such, the purpose of this project was to identify and describe the effectiveness of interventions to reduce ED visits for high-utilizers with CNCP.Methods : Included participants were high-utilizers presenting with CNCP. All study designs were eligible for inclusion if they examined an intervention aimed at reducing ED utilization. The outcomes of interest were the number of ED visits as well as the amount and type of opioids prescribed in the ED and after discharge. We searched Medline, EMBASE, CINAHL, CENTRAL, SCOPUS, Web of Science, and the grey literature from inception to June 16, 2018. Two independent investigators assessed articles for inclusion following PRISMA guidelines. Risk of bias will be assessed using the Cochrane ROBINS-I and RoB 2 tools for non-randomized and randomized trials, respectively.Results : Following review, 14 of the 5, 018 identified articles were included for analysis. These articles assessed a total of 1, 670 patients from both urban and rural settings. Interventions included pain protocols or policies (n = 5), individualized care plans (n = 5), ED care coordination (n = 2), a chronic pain management pathway (n = 1), and a behavioural health intervention (n = 1). Intervention effects trended towards the reduction of both ED visits and opioid prescriptions. The meta-analysis is in progress.Conclusion : Preliminary results suggest that interventions aimed at high-utilizers with CNCP can reduce ED visits and ED opioid prescription. ED opioid-restriction policies that sought to disincentivize drug-related ED visits were most successful, especially when accompanied by an electronic medical record (EMR) alert to ensure consistent application of the policy by all clinicians and administrators involved in the care of these patients. This review was limited by inconsistencies in the definition of 'high-utilizer' and by the lack of high-powered randomized studies.